The COVID‐19 pandemic and healthcare workers psychological well‐being: a cross‐sectional survey in Indonesia - Ni'matuzahroh; Valendriyani Ningrum; Widayat; Myrtati Dyah Artaria; Mein‐Woei Suen (Wiley, 2021)
Abstract Aim This study was conducted to investigate the relationships amongst psychological well‐being (PWB), emotional intelligence and coping strategies. Design This study employed a cross‐sectional survey design. Method A total of 146 healthcare workers (HCWs) were enrolled in this study. They were asked to finish several questionnaires, including the Wong and Law Emotional Intelligence Scale, the Brief‐Coping Orientation to Problems Experienced Scale and the PWB Scale. The obtained data were analysed using partial least squares structural equation modelling, employee SmartPLS, to estimate the contributions of influencing factors and evaluate the moderating effect of coping strategy (CS) on the relationship between emotional intelligence and PWB. Results Results revealed that emotional intelligence influenced PWB, and CS moderated both emotional intelligence and PWB. Furthermore, CS plays an essential role in improving PWB related to emotional intelligence amongst HCWs during the COVID‐19 outbreak.